The Effect of Peer Group Education on Blood Pressure Control in Patients with Hypertension: Literature Review - Masri Rahayu Putri; Reni Zulfitiri; Bayhakki Bayhakki (Indonesian Journal of Global Health Research, 2026)
Hypertension is a chronic disease with a high prevalence and is a major cause of global morbidity and mortality. Low medication adherence and inadequate patient knowledge are the main factors contributing to uncontrolled blood pressure. Peer group–based education has become one of the effective approaches to improving understanding, motivation, and health behavior changes among patients with hypertension. This review aims to comprehensively examine the effect of peer group education on hypertension control, including blood pressure, medication adherence, and lifestyle changes in patients with hypertension. This literature review used the PRISMA 2020 approach. Article searches were conducted through online databases including PubMed, ScienceDirect, and Google Scholar within the 2020–2025 publication period. The inclusion criteria comprised randomized controlled trials (RCTs), quasi-experimental, and experimental studies investigating peer group education interventions in adult patients with hypertension. A total of 7 articles published between 2022–2025 that met the inclusion criteria were critically appraised and analyzed descriptively and narratively to identify the effectiveness of peer group education interventions among patients with hypertension. The findings showed that peer group education significantly contributed to reducing blood pressure, improving medication adherence, and enhancing health behaviors such as dietary patterns, physical activity, and self-management. This intervention also improved patients' knowledge, motivation, and self-efficacy in managing hypertension. Peer group education is an effective intervention for hypertension control because it can improve adherence, promote healthier lifestyles, and reduce blood pressure.